2016
DOI: 10.4028/www.scientific.net/kem.695.309
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Collagen-Sodium Carboxymethylcellulose-Lidocaine 3D Composites for Wound Management

Abstract: A lot of biomaterials were investigated as suitable scaffolds for wound healing, very high costs being involved for treating their complications and consequences. Among them, a special attention is given to collagen, a natural biopolymer which showed positive effect on soft tissue regeneration. A key factor encountered in wound healing is represented by the pain control. Thus, the purpose of this study was to design and characterize some 3D composites based on collagen and lidocaine hydrochloride as anesthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recently research has demonstrated that lidocaine is not only able to decrease pain scores, analgesic consumption, and opioid side effects, but also promotes outcomes important for enhanced recovery after intervention. Clinical studies demonstrate analgesic, antihyperalgesic and anti-inflammatory properties of lidocaine [6,7].…”
mentioning
confidence: 99%
“…Recently research has demonstrated that lidocaine is not only able to decrease pain scores, analgesic consumption, and opioid side effects, but also promotes outcomes important for enhanced recovery after intervention. Clinical studies demonstrate analgesic, antihyperalgesic and anti-inflammatory properties of lidocaine [6,7].…”
mentioning
confidence: 99%